Implementasi prinsip hukum ekonomi syariah dalam sistem perbankan islam di indonesia - SUTIONO, DANI SUTIONO (Maliki Interdisciplinary Journal, 2025)
The standards of Sharia economic law serve as the establishment for Islamic managing an account operations in Indonesia. The usage of these standards points to form a reasonable, straightforward, and Sharia-compliant budgetary framework. This article talks about how Sharia economic law standards are connected within the Islamic keeping money framework, covering administrative angles, Sharia budgetary products, as well as challenges and openings in hone. Employing a subjective graphic strategy, this think about uncovers that strict controls and supervision by the Sharia Supervisory Board (DPS) play a vital part in guaranteeing compliance with Sharia. Be that as it may, challenges such as moo open education and constrained Sharia money related items stay impediments to the improvement of Islamic managing an account in Indonesia.